Cx3cr1 deficiency in mice attenuates hepatic granuloma formation during acute schistosomiasis by enhancing the M2-type polarization of macrophages - Lin Ran; Qilin Yu; Shu Zhang; Fei Xiong; Jia Cheng; Ping Yang; Jun-Fa Xu; Hao Nie; Qin Zhong; Xueli Yang; Fei Yang; Quan Gong; et al. (The Company of Biologists, 2015)
Acute schistosomiasis is characterized by pro-inflammatory responses against tissue- or organ-trapped parasite eggs along with granuloma formation. Here, we describe studies in Cx3cr1−/− mice and demonstrate the role of Cx3cr1 in the pathoetiology of granuloma formation during acute schistosomiasis. Mice deficient in Cx3cr1 were protected from granuloma formation and hepatic injury induced by Schistosoma japonicum eggs, as manifested by reduced body weight loss and attenuated hepatomegaly along with preserved liver function. Notably, S. japonicum infection induced high levels of hepatic Cx3cr1 expression, which was predominantly expressed by infiltrating macrophages. Loss of Cx3cr1 rendered macrophages preferentially towards M2 polarization, which then led to a characteristic switch of the host immune defense from a conventional Th1 to a typical Th2 response during acute schistosomiasis. This immune switch caused by Cx3cr1 deficiency was probably associated with enhanced STAT6/PPAR-γ signaling and increased expression of indoleamine 2,3-dioxygenase (IDO), an enzyme that promotes M2 polarization of macrophages. Taken together, our data provide evidence suggesting that CX3CR1 could be a viable therapeutic target for treatment of acute schistosomiasis.